A study on the consumer behaviour and the place of consumer cooperatives in a rural area - Nakkiran, S., 1945- (Dept. of Cooperation, Tranquebar Bishop Manikam Lutheran College, 1977)
Socio-economic study of Porayar, a village in Kerala.